Perbandingan Sistem Pajak E-Commerce di Indonesia dengan Negara Lain - Susmala, Windy Fatma; Jadidah, Wanti Nur; Pahala, Indra; Wahono, Puji (Transpublika Publisher, 2025)
This study aims to compare the e-commerce taxation system in Indonesia with several other countries that have already implemented digital tax policies. With the rapid development of the e-commerce sector, Indonesia faces a major challenge in creating regulations that can accommodate cross-border transactions and ensure tax compliance from local and foreign business actors. This study discusses the main differences between the tax systems implemented in Indonesia and countries such as the European Union, the United States, Australia, and Singapore. The main focus of this study is to analyze the differences in the types of taxes, collection mechanisms, and their impacts on entrepreneurs and state revenues. This study uses a quantitative descriptive approach with secondary data obtained from government reports and academic sources, as well as a survey of e-commerce actors in Indonesia. The results of this study are expected to provide insights for improving tax policies in Indonesia, especially in aligning the digital taxation system with global trends.